Subtyping patients with somatic tinnitus: Modulation of tinnitus and history for somatic dysfunction help identify tinnitus patients with temporomandibular joint disorders - Ralli, Massimo; Greco, Antonio; Boccassini, Armando; Altissimi, Giancarlo; Di Paolo, Carlo; Falasca, Vincenzo; De Virgilio, Armando; Polimeni, Antonella; Cianfrone, Giancarlo; de Vincentiis, Marco (PLOS ONE, 2018)
Objective Determine in a cohort of patients with normal hearing and chronic tinnitus if self-reported history for temporomandibular joint (TMJ) dysfunction and a positive modulation of tinnitus in the TMJ region could be suggestive of an underlying TMJ disorder. Patients and methods The study included 226 patients presenting to the Head and Neck Service of our University Hospital. Following audiological and somatic tinnitus evaluation, patients were divided into two groups. The study group (n = 134) included subjects that met both the following criteria: A) a self-reported history for TMJ dysfunction and B) a positive modulation of tinnitus following somatic maneuvers in the TMJ region. The control group (n = 92) included patients with similar demographic and tinnitus characteristics that did not meet the proposed criteria for somatic tinnitus. Afterwards, patients underwent clinical TMJ evaluation in the Service of Clinical Gnathology of our University. Results One hundred thirty-one patients (57.9%) received a clinical diagnosis of TMJ disorder according to DC/TMD Axis I; 79.1% in the study group and 27.2% in the control group. Ninety-five (42.1%) patients were negative for TMJ disorders; 20.9% in the study group and 72.8% in the control group. A significantly higher number of TMJ disorders was found in patients in the study group compared to the control group (p<0.0001). Most patients had joint disorders (67.2%), followed by other (29.8%) and pain disorders (29%). Logistic regression analysis in the study group showed that female gender was more prevalent in patients with TMJ disorders. Conclusion Our findings in patients with chronic tinnitus and normal hearing suggest that self-reported history for somatic dysfunction and modulation of tinnitus, when occurring simultaneously in the TMJ region, can be useful to preliminarily identify patients with TMJ disorders.